Determinants of Breastfeeding at Discharge in Rural China - Tang, Li; Binns, Colin; Luo, C.; Zhong, Z.; Lee, Andy (HEC Press, 2013)
This study aimed to investigate the rate of breastfeeding at discharge and associated influencing factors in rural China. A prospective cohort study of infant feeding practices was undertaken during 2010-2011 in Jiangyou city, Sichuan Province of China. Logistic regression analysis was performed to ascertain pertinent factors affecting the prevalence of any breastfeeding at discharge. The participants consisted of 695 mothers aged 18-44 years. The breastfeeding rate at discharge was 93.5% (95% CI: 91.7-95.3). Perceived paternal breastfeeding preference was positively associated with actual breastfeeding at discharge (OR=4.46, 95% CI: 2.15-9.28). Other significant determinants were ‘receiving breastfeeding support’ from staff during hospital stay (OR=3.41, 95% CI: 1.58-7.34) and making the decision on feeding method during pregnancy or after childbirth (OR=0.46, 95% CI: 0.22-0.93). In conclusion, provision of comprehensive breastfeeding support in hospital and education programs targeting expectant and future parents are recommended to further increase the rate of breastfeeding at discharge in rural areas of China.